1986
DOI: 10.3171/jns.1986.65.1.0044
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial surgical approaches to the orbital part of the optic nerve: an anatomical study

Abstract: The authors have identified and described three transcranial approaches to the intraorbital portion of the optic nerve. The structures encountered in these approaches are demonstrated under magnification in cadavers, and the exposure of the optic nerve is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…The severe of cavernous sinus hemorrhage is life-threatening. However, the less serious case with a small rupture can be cured endoscopically [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The severe of cavernous sinus hemorrhage is life-threatening. However, the less serious case with a small rupture can be cured endoscopically [7].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the main regions to bear external force, many physicians [7] divided the optic nerve injuries into three types [8]: the external type (the force bearing region is the external part of superciliary arch), the medial type (the force bearing region is the frontal part of superciliary arch), and the zygomatic type (the force bearing region is the zygomatic bone). The authors found out that OAS could also be divided into the aforesaid three types according to force bearing regions, and the medial type achieved better results than the external and zygomatic types after decompression of the cranial nerves, and there was no significant difference between the therapeutic results in the external type and that in the zygomatic type (no significant statistics are available because of only 2 cases).…”
Section: Discussionmentioning
confidence: 99%
“…The massive hemorrhage caused by a cavernous sinus injury could be life-threatening. If the fistula of the sinus is small, it can be repaired completely via endoscope [17].…”
Section: Discussionmentioning
confidence: 99%
“…The superior division continues medially to innervate superior rectus likewise the frontal nerve. They can be both retracted medially together with levator palpebrea superioris but this makes only the middle one‐third of the upper part of the cone to be exposed and may hinder axes to orbital apex (Blinkov et al, ; Natori and Rhoton, ). Zhang et al () revealed the transition point of the muscular branches of the superior divsion to be located proximally in the middle of the orbit, and suggested using this point as a landmark.…”
Section: Discussionmentioning
confidence: 99%